Astronomy : the study of the universe - Mahoney, Terry (Milwaukee, WI : Gareth Stevens Pub., 2002)
Examines the science of astronomy and how it reveals the secrets of the universe.
Includes bibliographical references and index.
Horn Book.
6.8
3-6
Keywords: Astronomy -- Juvenile literature; Astronomy; Astronomy